The Psychobiology of Bereavement and Health: A Conceptual Review From the Perspective of Social Signal Transduction Theory of Depression - Seiler, Annina; von Känel, Roland; Slavich, George M. (Frontiers in Psychiatry, 2020)
Losing a spouse is considered one of the most stressful life events a person can experience. Particularly in the immediate weeks and months after the loss, bereavement is associated with a significantly increased risk of morbidity and mortality. Despite an abundance of research aimed at identifying risk factors for adverse health outcomes following marital death, though, the mechanisms through which mental and physical health problems emerge following bereavement remain poorly understood. To address this issue, the present review examines several pathways linking bereavement and health, including inflammation and immune dysregulation, genetic and epigenetic changes, gut microbiota activity, and biological aging. We then describe how these processes may be viewed from the perspective of the Social Signal Transduction Theory of Depression to provide a novel framework for understanding individual differences in long-term trajectories of adjustment to interpersonal loss. Finally, we discuss several avenues for future research on psychobiological mechanisms linking bereavement with mental and physical health.